DYNAMICS OF THE LEVEL OF INFLAMMATION MARKERS IN PATIENTS WITH FRACTURES OF LONG BONES AGAINST THE BACKGROUND OF COVID-19 - Tanasiienko, P.V.; Guriev, S.O.; Skobenko, E.O. (World of Medicine and Biology, 2024)
The purpose of the study was to determine the response dynamics of inflammatory markers C-reactive protein and procalcitonin in patients with long bone fractures against the background of COVID-19. The main group included 157 cases of skeletal fractures against the background of COVID-19, and the control group included 132 cases of skeletal fractures in which there was no COVID-19 infection. The dynamics of the C-reactive protein level in patients with fractures against the background of COVID-19 indicated that this inflammatory marker is not informative at the initial stage, however, starting from the 3rd day, a significant increase in the C-reactive protein level was noted with a subsequent drop in the level in the postoperative period on the 10th day of treatment. The dynamics of the procalcitonin level was approximately the same during all observation periods and did not reflect the changes that occurred in patients with long bone fractures against the background of COVID-19, which does not allow the use of this inflammatory marker in the clinical diagnosis of the course of COVID-19 in patients with long bone fractures
Keywords: trauma; COVID-19; C-reactive protein; procalcitonin